ANALISIS PENGARUH ADVERTISING,PERSONAL SELLING DAN SALES PROMOTION PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Yulasmi, Yulasmi (Jurnal Ekobistek, 2014)
Abstract - This research aims to find out how big the influence of Advertising, Personal Selling, and the simultaneous and partial Sales Promotion of the purchase decision, using the method of collection of data that is in the form of a detailed questionnaire and analysis of the methods used was multiple linear regression analysis. Based on the Partial Test results (t test) test results of the regression coefficients obtained, Advertising has t count> t table (6,285> 1.98580), meaning that a significant difference between the buying decision Advertising. Personal Selling has t count> t table (3.311> 1.98580), meaning that a significant difference between Personal Selling the Buying Decision. Sales Promotion has t count> t table (5,536> 1.98580), meaning that a significant difference between Sales Promotion with Purchase Decision. Then based on the simultaneous test (Test F) can be known value Fhitung 206 787> f_tabel 2.70, meaning that the variable Advertising, Personal Selling, and Sales promotion significant effect jointly to variable purchase decision. And by testing the coefficient of determination (R2) value was 0.866. This shows that the percentage contribution of variable Advertising, Personal Selling, and Sales Promotion on Purchase Decision variable is equal to 86.6% and the remaining 13.4% is influenced by other variables not included in the variables studied. Key words : Advertising, Personal Selling, Sales Promotion and Purchases Decision